2014
DOI: 10.1155/2014/489289
|View full text |Cite
|
Sign up to set email alerts
|

MNDWSN for Helping People with Different Disabilities

Abstract: This paper introduces a monitoring and navigation system to help people with disabilities (MND WSN ). The proposed system is based on wireless sensor networks. In the MND WSN system, each disabled person uses a handheld smart phone device. Three types of disabilities are studied in this paper: (1) blind, (2) deaf, and (3) on wheelchair. We experimented with a three-floor university building. Sensor nodes and cameras are scattered in all rooms and hallways. Smart phones are used to communicate with the sensor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
1
0
3
Order By: Relevance
“…As shown in Table 3, it was found that if the RSSI is lower than −20, this means that a disabled person is moving for detection. These values were used to trigger cameras used for monitoring the disabled person [17]. Older disabled persons are usually slower than younger ones as shown in Table 3.…”
Section: Reference and Lmn4disabled Resultsmentioning
confidence: 99%
“…As shown in Table 3, it was found that if the RSSI is lower than −20, this means that a disabled person is moving for detection. These values were used to trigger cameras used for monitoring the disabled person [17]. Older disabled persons are usually slower than younger ones as shown in Table 3.…”
Section: Reference and Lmn4disabled Resultsmentioning
confidence: 99%
“…O sistema de monitoramento e navegação MNDWSN [7] baseia-se em redes de sensores sem fio WSN (do inglês Wireless Sensor Network) e smartphones. O objetivo do MNDWSN é oferecer auxílio para cegos, surdos e pessoas com deficiência nos membros inferiores e superiores, auxiliando no deslocamento em ambientes internos.…”
Section: Trabalhos Relacionadosunclassified
“…Trabalhos desenvolvidos neste segmento não fazem uso das informações geradas pelas interações das PcDs, gerenciam locais restritos não incluindo recursos dinâmicos e não atendem situações com grande número de PcDs [7,23,26,35,44]. O MASC (do inglês a computational Model for Accessibility in Smart Cities) auxilia PcDs, gerencia contextos [18], recursos, perfis [46] das PcDs, atende aplicações massivas e armazena históricos [33] formando trilhas [6].…”
Section: Introductionunclassified
See 1 more Smart Citation